Benefits of protected areas for nonbreeding waterbirds adjusting their distributions under climate warming. Issue 3 (21st January 2021) - Gaget, Elie; Pavón‐Jordán, Diego; Johnston, Alison; Lehikoinen, Aleksi; Hochachka, Wesley M.; Sandercock, Brett K.; Soultan, Alaaeldin; Azafzaf, Hichem; Bendjedda, Nadjiba; Bino, Taulant; Božič, Luka; Clausen, Preben; et al.
Abstract: Climate warming is driving changes in species distributions and community composition. Many species have a so‐called climatic debt, that is, shifts in range lag behind shifts in temperature isoclines. Inside protected areas (PAs), community changes in response to climate warming can be facilitated by greater colonization rates by warm‐dwelling species, but also mitigated by lowering extirpation rates of cold‐dwelling species. An evaluation of the relative importance of colonization‐extirpation processes is important to inform conservation strategies that aim for both climate debt reduction and species conservation. We assessed the colonization‐extirpation dynamics involved in community changes in response to climate inside and outside PAs. To do so, we used 25 years of occurrence data of nonbreeding waterbirds in the western Palearctic (97 species, 7071 sites, 39 countries, 1993–2017). We used a community temperature index (CTI) framework based on species thermal affinities to investigate species turnover induced by temperature increase. We determined whether thermal community adjustment was associated with colonization by warm‐dwelling species or extirpation of cold‐dwelling species by modeling change in standard deviation of the CTI (CTISD ). Using linear mixed‐effects models, we investigated whether communities in PAs had lower climatic debt and different patterns of community change than communities outside PAs. For CTI and CTISD combined, communities inside PAs had more species, higher colonization, lower extirpation, and lower climatic debt (16%) than communities outside PAs. Thus, our results suggest that PAs facilitate 2 independent processes that shape community dynamics and maintain biodiversity. The community adjustment was, however, not sufficiently fast to keep pace with the large temperature increases in the central and northeastern western Palearctic. Our results underline the potential of combining CTI and CTISD metrics to improve understanding of the colonization‐extirpation patterns driven by climate warming. Abstract : Article impact statement : Protected areas are needed to facilitate waterbird distribution change in response to climate warming in the western Palearctic. Abstract : Beneficios de las Áreas Protegidas para las Aves Acuáticas No Reproductoras que Están Ajustando su Distribución Debido al Calentamiento Climático Resumen: El calentamiento climático está generando cambios en la distribución y en la composición comunitaria de las especies. Muchas de ellas tienen una deuda climática, es decir, los cambios en la distribución se atrasan con respecto a los cambios en las isoclinas térmicas. Dentro de las áreas protegidas (APs), los cambios comunitarios como respuesta al calentamiento climático pueden facilitarse mediante tasas mayores de colonización por especies de climas cálidos, pero también pueden mitigarse al reducir las tasas de extirpación de las especies de climas fríos. Se requiere una evaluación de la importancia relativa de los procesos de colonización‐extirpación para orientar las estrategias de conservación que buscan la reducción de la deuda climática y la conservación de las especies. Analizamos las dinámicas de colonización‐extirpación que participan en los cambios comunitarios como respuesta al clima dentro y fuera de las APs. Para realizar lo anterior, usamos datos tomados durante 25 años de la presencia de aves acuáticas no reproductoras en el Paleártico occidental (97 especies, 7, 071 sitios, 39 países, 1993–2017). Usamos un marco de trabajo del índice de temperatura comunitaria (ITC) basado en las afinidades térmicas de las especies para así investigar la rotación de especies inducida por el incremento en la temperatura. Determinamos si el ajuste térmico en la comunidad estuvo asociado con la colonización por especies de climas cálidos o con la extirpación de especies de climas fríos al modelar el cambio mediante una desviación estándar del ITC (ITCDS ). Con los modelos lineales de efectos mixtos investigamos si las comunidades dentro de las APs tenían una deuda climática más baja y patrones diferentes de cambio comunitario que las comunidades localizadas fuera de las APs. Con la combinación del ITC y deL ITCDS, las comunidades dentro de las APs tuvieron más especies, una mayor colonización, una menor extirpación y una deuda climática más baja (16%) que las comunidades fuera de las APs. Por lo tanto, nuestros resultados sugieren que las APs facilitan dos procesos independientes que moldean las dinámicas comunitarias y mantienen la biodiversidad. Sin embargo, el ajuste comunitario no fue lo suficientemente rápido para mantener el paso de los grandes incrementos en la temperatura de las regiones central y noreste del Paleártico occidental. Nuestros resultados resaltan el potencial que tiene la combinación de las medidas del ITC y del ICTDS para mejorar el entendimiento de los patrones de colonización‐extirpación causados por el calentamiento climático. 【摘要】: 气候变暖正在引起物种分布和群落组成的变化。许多物种都背负着所谓的 "气候债务", 即分布范围的变化滞后于温度的变化。气候变暖背景下, 保护地中适应温暖环境的物种较高的定殖率可以促进群落变化, 适应寒冷环境的物种灭绝率下降也可以减缓影响。评估定殖–灭绝过程的相对重要性, 对于制定旨在减少气候债和促进物种保护的保护战略而言十分重要。本研究利用西古北界非繁殖水鸟 25 年的出现记录 (97 个物种, 7071 个位点, 39 个国家, 1993–2017 年), 评估了保护地内外鸟类群落响应气候变化过程中的定殖–灭绝动态。我们使用基于物种对温度亲和性的群落温度指数框架探究了温度升高引起的物种更替。通过模拟群落温度指数标准偏差的变化, 我们确定了群落对温度的调整是否与适应温暖环境的物种的定殖或适应寒冷环境的物种的灭绝有关。接下来, 我们利用线性混合效应模型分析了保护地内与保护地外的群落相比是否具有较低的气候债务和不同的群落变化格局。结合群落温度指数与其标准偏差, 我们发现保护地内的群落比保护地外的具有更多的物种、更高的定殖率、更低的灭绝率和更低的气候债务 (16%) 。因此, 我们的结果表明, 保护地促进了群落动态形成和生物多样性维持这两个独立过程。然而, 群落调整的速度不足以跟上古北界中部和东北部地区气温的大幅上升。我们的结果强调了群落温度指数和群落温度指数标准偏差这两个指标相结合, 有潜力提高对气候变暖导致的定殖–灭绝格局的理解。【翻译: 胡怡思; 审校: 聂永刚】